2010
DOI: 10.1007/s10800-010-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on simultaneous measurements of trace gallium(III) and germanium(IV) by adsorptive stripping voltammetry using mercury film electrode

Abstract: Simultaneous adsorptive stripping voltammetric method for the determination of trace gallium(III) and germanium(IV) based on the adsorption of gallium(III) and germanium(IV)-catechol complex on the cyclic renewable mercury film silver based electrode (Hg(Ag)FE) is presented. The calibration graph is linear from 1.25 nM (0.09 lg L -1 ) to 90 nM (6.27 lg L -1 ) with correlation coefficient of 0.999 for gallium and from 2.5 nM (0.18 lg L -1 ) to 160 nM (12.3 lg L -1 ) with correlation coefficient of 0.998 for ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In the previous paper 17 we proved that cupferron forms stable complexes with gallium and in comparison with other complexing agents, such as solochrome violet RS 14, morin 15, ammonium pyrrolidine dithiocarbamate (APDC), pyrocatechol violet (PCV), diethyldithiocarbamate (DDTC) 16, alizarin red S 20, catechol 18, 19 that have been used so far in voltammetric procedures of gallium determination provides the best parameters, such as the widest linear range and the lowest detection limit. Preliminary experiments confirmed that Ga(III)‐cupferron complexes also adsorbed on the in situ plated lead electrode so the optimization of experimental parameters in the determinations, such as the composition of the supporting electrolyte, cupferron concentration, conditions of lead film formation, potential and time of accumulation was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous paper 17 we proved that cupferron forms stable complexes with gallium and in comparison with other complexing agents, such as solochrome violet RS 14, morin 15, ammonium pyrrolidine dithiocarbamate (APDC), pyrocatechol violet (PCV), diethyldithiocarbamate (DDTC) 16, alizarin red S 20, catechol 18, 19 that have been used so far in voltammetric procedures of gallium determination provides the best parameters, such as the widest linear range and the lowest detection limit. Preliminary experiments confirmed that Ga(III)‐cupferron complexes also adsorbed on the in situ plated lead electrode so the optimization of experimental parameters in the determinations, such as the composition of the supporting electrolyte, cupferron concentration, conditions of lead film formation, potential and time of accumulation was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore as an alternative stripping approach for trace quantitation of gallium the adsorptive cathodic stripping voltammetry (AdCSV) can been applied. In this case also mercury electrodes are mainly used, HMDE 1417 or Hg(Ag)FE 18, 19. In literature data we found only one adsorptive voltammetric procedure for gallium determination using mercury free electrode, that is carbon paste electrode 20.…”
Section: Introductionmentioning
confidence: 99%
“…To study interferences, earlier studies have investigated the inuence by adding interfering ions, surface-active compounds and EDTA. 41 However, the compounds from the diluted acid extraction solution cannot be simply simulated by adding the chemicals mentioned above.…”
Section: Matrix Interferencesmentioning
confidence: 99%
“…For the AdSV quantification of Ga(III) or-simultaneously-Ga(III) and Ge(IV) at the Hg(Ag)FE-c, complexes of these metal ions with catechol were employed [55]. The methods, characterized by low LODs, were successfully applied to determine the concentration of these metals in water and sediment samples.…”
Section: Adsorptive Stripping Voltammetrymentioning
confidence: 99%